Analisa Kebutuhan Ruang Pandangan Bebas Pada Perlintasan Sebidang Tanpa Palang Pintu Di Desa Gelam, Kabupaten Sidoarjo - Nugroho Utomo (Sekolah Tinggi Teknik - PLN, 2021)
Railway crossing are amongst the most complex of road safety handling systems, due to the conflicts between road vehicles and rail infrastructure operations. Railway crossing until now is still become the one of major accident cause for road users. Mainly caused by indiscipline acts of road users when pass a railway crossing such as opening an illegal crossing, trespassing closed crossing gate and unaware road users. In the area that growing into an industrial and commercial area, the origins of road network that is local road type changed to collector road type. This roads transformation affected to appears of unprotected railway level crossings which existing railways and roads are closed to each other. In Province of East Java especially at Sidoarjo Municipality there are two railway crossing which indicating to this serious matters located at JPL 69 Gelam 1 and JPL 70 Gelam 2. These two railway crossing showing an incomplete standard safety facilities which required such as railway warning sign and others. By this urgency, paperwork is held to discussing about standard safety facilities identifications and analyzing availability of clear visible zone according with Guidance of Technically Design of Railway Crossing. As a results explained that JPL 69 Gelam 1 is not recommended for safety reasons and JPL 70 Gelam 2 is recommended with several conditions that must be equipped.